Positioning algorithm based on improved dragonfly optimization - Zhang, Yue; Pu, Hongping; Chen, Wei (International Journal of Computer Science and Information Technology, 2023)
Aiming at solving the nonlinear equation of indoor arrival time difference positioning, a multi-strategy improved dragonfly optimization algorithm is proposed. The initial population is improved by chaotic mapping, and then nonlinear factors and Cauchy mutation operators are introduced to rapidly converge the balanced global search and local search. At the same time, simulation and comparison experiments with other algorithms show that the algorithm has a higher positioning effect.